Infraglottic versus supraglottic jet-ventilation for endobronchial ultrasound-guided transbronchial needle aspiration: A randomised controlled trial. Issue 11 (November 2020) - Anwar, Maria; Fritze, Robert; Base, Eva; Wasserscheid, Thomas; Wolfram, Nadja; Koinig, Herbert; Hackner, Klaus; Lambers, Christopher; Schweiger, Thomas; Errhalt, Peter; Hoda, Mir A.
Abstract : BACKGROUND: For endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) under general anaesthesia, both rigid bronchoscopy and laryngeal masks (LMAs) with superimposed high-frequency jet ventilation can be used. Despite the fact that in Europe rigid bronchoscopy for EBUS-TBNA is still widely used, an increasing number of centres use jet ventilation via the LMA for this procedure. To our knowledge no clinical trials have ever been made to compare these two methods. This trial aimed to evaluate whether patients recover from the procedure more quickly when a LMA is used for ventilation compared with rigid bronchoscopy where muscle relaxants and deep anaesthesia are required. OBJECTIVES: We wanted to test the hypothesis that there is no difference in the postoperative recovery of patients in the postanaesthesia care unit (PACU) after EBUS-TBNA with jet ventilation via a rigid bronchoscope and a LMA. Secondary outcomes were the difference of duration of anaesthesia, the diagnostic outcome of the procedure and drug quantities for both groups. DESIGN: Prospective randomised single blinded two centre controlled trial. SETTING: Two centres in Austria participated. Patients were enrolled from December 2016 until January 2018. PATIENTS: Ninety patients for elective EBUS-TBNA were enrolled and assigned to one of two intervention groups. Two patients were excluded before and eleven patients were excluded after EBUS-TBNA. Seventy-seven were analysed. INTERVENTIONS: Patients assigned to group 1 were ventilated with a LMA; those assigned to group 2 were ventilated via a rigid bronchoscope. Vital signs, drug dosage, duration of anaesthesia, recovery, PACU stay and Aldrete score at the PACU were recorded. MAIN OUTCOME MEASURES: The primary endpoint was an integral over time of a modified Aldrete score. Secondary endpoints were the durations of the interventions, the recovery from anaesthesia and PACU stay, initial and mean Aldrete values at PACU, the effect site concentration of Propofol according to the Schnider pharmacokinetic model, the peak ultiva rates and the diagnostic outcome. RESULTS: We were not able to show any significant difference regarding the postoperative recovery criteria based on the Aldrete score, the durations measured and the diagnostic outcomes. Vital signs remained stable and in an equal range in both groups. There were no differences in the mean effect site propofol concentration and the peak ultiva rates. CONCLUSION: EBUS-TBNA under general anaesthesia using a LMA with SHJV is equal to rigid bronchoscopy with superimposed high-frequency jet ventilation for the variables analysed. TRIAL REGISTRATION: ISRCTN (ISRCTN58911367). Abstract : Supplemental Digital Content is available in the text